PENGGUNAAN SIMULASI PhET SEBAGAI MEDIA PENGAJARAN UNTUK MENINGKATKAN PEMAHAMAN SISWA DAN MOTIVASI DALAM PEMBELAJARAN TATA SURYA - Putri, Aldia Ridwani (2017)
This research investigated the implementation of PhET simulation on students' understanding and motivation in learning Solar system. The method used in this research was quasi experimental with matching pretest-posttest group design. The research conducted in one of private Junior HighSchool located at Padalarang, West Bandung with number of students(n=42). The sampling technique used was random cluster sampling to determine experimental group with PhET simulation in the learning science and control groupwithout PhET simulation. The quantitative data of this research was obtained through objective test on mastery concept Solar system, while the qualitative data was detected through motivation rubric and questionnaire. The result shows that the students who learn Solar system with PhET simulation have higher both improvement in conceptual understanding and motivation than without PhET simulation as teaching media. According to analysis result, there is correlation between conceptual understanding and motivation with the learning Solar system in the use PhET simulation. The criteria of correlation this research is middle (0.25-0.50). Because of twenty-one of students are only six students who get high score in objective test and high motivated of students' response in using PhET simulation. Key words: PhET simulation, Solar system, Students' motivation, Students' understanding, PenelitianinibertujuanuntukmenyelidikipengunaansimulasiPhETpadapemahamansiswadanmotivasidalampembelajaran Tata Surya.Metode yang digunakandalampenelitianiniadalahkuasieksperimendengandesainpenelitian Matching only pretest-posttest group. PenelitiandilakukanpadasatusekolahswastaSekolahMenengahPertama yang berlokasi di Padalarang, Bandung Barat denganjumlahsiswanyasebanyak (n=25). Teknikpengambilansampel yang digunakanadalahrandom cluster samplinguntukmenentukankelompokeksperimendengansimulasiPhETdalampembelajaran IPA dankelompokkontrol yang tanpapenggunaansimulasiPhET.Data kuantitatifdaripenelitianinididapatkanmelaluitesobjektiftentangkonsep Tata Surya, sedangkan data kualitatifdiperolehmelalui rubric motivasi and kuisioner.Hasilpenelitianmenunjukkanbahwasiswa yang belajar Tata Surya dengansimulasiPhETlebihmeningkatdalampemahamankonseptualdanmotivasidaripadatanpasimulasiPhETsebagai media pengajaran.Sesuaidenganhasilanalisisterdapathubunganantarapemahamankonseptualdanmotivasidalampembelajaran Tata Surya melaluipenggunaansimulasiPhET.Kriteiakorelsidalampenelitianiniadalahkorelasicukup (0.25-0.50).Karenadariduapuluhsatusiswa yang hanyamendapatnilaitertinggidalamobjektif test danmemilikimotivasitinggidalamresponsiswadalampenggunaanPhETsimulasi. Key words:SimulasiPhET, Tata Surya, MotivasiSiswa, Pemahamansiswa